Estrogen-regulated PTTG1 promotes breast cancer progression by regulating cyclin kinase expression - Chunhui Meng; Yan Zou; Weiwei Hong; Chunhua Bao; Xiaofeng Jia (BMC, 2020)
Abstract Background The present study aims to investigate the effects of pituitary tumor transforming gene (PTTG) 1 on breast cancer and its underlying mechanism. Methods GEO data set was applied to analyze the relationship between PTTG1 and survival status and the TCGA breast cancer dataset was used to explore its possible targets. The stable cell lines including PTTG1 knockdown cells, estrogen receptor (ESR) 1 knockdown cells, and PTTG1 overexpression cells were constructed. MTT was used to determine cell viabilities. Propidium iodide (PI) staining and flow cytometry were used to analyze the cell cycle. Quantitative polymerase chain reaction (qPCR) was employed to determine the mRNA expressions. Points mutations and luciferase reporter assays were used to determine the binding sites of estrogen. Results PTTG1 was associated with poor survival rates in breast cancer. In vitro study demonstrated that PTTG1 affected cell viabilities of MCF7 and T47D cells. Besides, PTTG1 affected cell cycle arrest of breast cancer cells. Overexpression of PTTG1 led to more breast cancer cells distributed in S phase. The levels of PTTG1 were associated with estrogen and further results showed that the levels of PTTG1 were positively correlated to tamoxifen resistance. Two genes including CCNA2 and CCNB2 were identified to be possible targets of PTTG1. Conclusion Estrogen-regulated PTTG1 promotes the development of breast cancer cells by the regulation of the cell cycle.